Electron microscopy, XRD, dielectric, and Mossbauer studies of Li-doped Pb(Fe0.5Nb0.5)O3 ceramics sintered from mechanically activated powders. Issue 1 (27th May 2016) - Gusev, A. A.; Raevskaya, S. I.; Raevski, I. P.; Isupov, V. P.; Avvakumov, E. G.; Kubrin, S. P.; Chen, H.; Titov, V. V.; Minasyan, T. A.; Chou, C.- C.; Titov, S. V.; Malitskaya, M. A.
ABSTRACT: X-ray diffraction (XRD) studies of the phases formed on the surface of the Li-doped PbFe0.5 Nb0.5 O3 (PFN) ceramics sintered under different conditions from the mechanically activated mixture of oxides and Li2 CO3 have been carried out. At sintering temperatures exceeding 800°C a partial evaporation of PbO leads to the formation of pyrochlore Pb2 Fe4 Nb4 O21 and lithium ferrites LiFeO2 and LiFe5 O8 phases in the surface layer about 100 μm thick. An increase of the Neel temperature by more than 40 K, as compared to single crystal, was achieved in the mechanically activated PFN powder sintered at 600°C.